Potentially severe drug-drug interactions among older people and associations in assisted living facilities in Finland: a cross-sectional study - Mariko Teramura-Grönblad; Minna Raivio; Niina Savikko; Seija Muurinen; Helena Soini; Merja Suominen; Kaisu Pitkälä (Taylor & Francis Group, 2016)
Objective: This study aims to assess potentially severe class D drug-drug interactions (DDDIs) in residents 65 years or older in assisted living facilities with the use of a Swedish and Finnish drug-drug interaction database (SFINX). Design: A cross-sectional study of residents in assisted living facilities in Helsinki, Finland. Setting: A total of 1327 residents were assessed in this study. Drugs were classified according to the Anatomical Therapeutic Chemical (ATC) classification system and DDDIs were coded according to the SFINX. Main outcome measures: Prevalence of DDDIs, associated factors and 3-year mortality among residents. Results: Of the participants (mean age was 82.7 years, 78.3% were females), 5.9% (N = 78) are at risk for DDDIs, with a total of 86 interactions. Participants with DDDIs had been prescribed a higher number of drugs (10.8 (SD 3.8) vs. 7.9 (SD 3.7), p < 0.001). A larger proportion of residents with DDDIs suffered from rheumatoid arthritis or osteoarthritis than those not exposed to DDDIs (24.7% vs. 15.4%, p = 0.030). The most frequent DDDIs were related to the concomitant use of potassium with amiloride (N = 12) or spironolactone (N = 12). Carbamazepine (N = 13) and methotrexate (N = 9) treatments were also frequently linked to DDDIs. During the follow-up, no differences in mortality emerged between the participants exposed to DDDIs and the participants not exposed to DDDIs. Conclusions: Of the residents in assisted living, 5.9% were exposed to DDDIs associated with the use of a higher number of drugs. Physicians should be trained to find safer alternatives to drugs associated with DDDIs.KEY POINTS   Potentially severe, class D drug-drug interactions (DDDIs) have been defined in the SFINX database as clinically relevant drug interactions that should be avoided.  • Of the residents in assisted living, 5.9% were exposed to DDDIs that were associated with the use of a higher number of drugs.  • The most frequent DDDIs were related to the concomitant use of potassium with amiloride or spironolactone. Carbamazepine and methotrexate were also linked to DDDIs.  • No difference in mortality was observed between residents exposed to DDDIs and residents not exposed to DDDIs.